Plate Vibration under Irregular Internal Supports - ZHAO, Yibao (Institutional Knowledge at Singapore Management University, 2002)
This paper studies the problem of plate vibration under complex and irregular internal support conditions. Such a problem has its widely spread industrial applications and has not been addressed in the literature yet, partially due to the numerical difficulties. A novel computational method, discrete singular convolution (DSC), is introduced for solving this problem. The DSC algorithm exhibits controllable accuracy for approximations and shows excellent flexibility in handling complex geometries, boundary conditions and internal support conditions. Convergence and comparison studies are carried out to check the validity and accuracy of the DSC method. Case studies are considered to the combination of a few different boundary conditions and irregular internal supports. The latter are generated by using an image processing algorithm. Completely independent verifications are conducted by using the established pb-2 Ritz method, which is available for two relatively simpler support patterns. The morphology of the first few eigenmodes is found to be localized to largest support-free spatial regions.